The Effect of Price and Taste on Wizzmie Customer Satisfaction in Surabaya - Ananda Rizqi Johansyah (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
Consumer satisfaction is very important for sellers because consumers who are satisfied with the product or service used means that the seller has good performance. Consumers who are satisfied with a product will increase selling power because these consumers will return again to become regular customers. Sellers are required to create strategies that can create satisfaction for consumers such as service quality and pricing according to the products provided. This study aims to determine the effect of price and taste partially on customer satisfaction at Wizzmie restaurant in Surabaya and to determine the effect of price and taste simultaneously on customer satisfaction at Wizzmie restaurant in Surabaya. This research method uses a quantitative descriptive type, namely research by emphasizing its analysis on numerical data that are processed using a statistical model. The type of research data used in this research is quantitative data. The sample in this study were 40 respondents, namely consumers who bought at the WIzzmie restaurant in Surabaya. The results showed that (1) there was no effect between price and consumer satisfaction at the Wizzmie restaurant in Surabaya. (2) There is a significant positive effect between taste and consumer satisfaction of 49.8%. So it can be concluded that taste affects consumer satisfaction at the Wizzmie restaurant in Surabaya. (3) There is a significant positive effect between price and taste simultaneously on customer satisfaction at the Wizzmie restaurant in Surabaya.